Phytoncide: Nature’s Antidote for Humanity - Anu Sreedevi; Sethu R (International Journal of Ayurveda and Pharma Research, 2024)
Nature is considered as a mighty healer for human beings since ages. It is undoubtful that Plants offers a plentiful reservoir of medicinal compounds. Among these, secondary metabolites are the phytochemicals produced as a result of protection against pathogens, herbivorous animals, and other environmental stress factors. Phytoncides are Volatile Organic Compounds (VOC’s) produced by the plants in order to protect themselves from bacteria, fungi, insects and other organisms and are released into the air, thereby forming a protective environment around the plant. These phytoncides which are mostly of isoprene origin has exhibited various pharmacological activities. Researches have found that forest bathing or prolonged exposure to forest volatile oils can have a profound impact on both physical and mental well being of humans. Since these chemicals act mainly by stimulating olfactory receptors and interacting with nasal mucous membranes, they can be considered similar to aromatherapy. Aromatherapy basically works through olfactory system as well as through dermal absorption. Both share some general health benefits like enhancing immunity by increasing NK cell activity and reducing the mental stress. Recently, many expert scientists around the world has developed new concepts like forest medicine and forest therapy, which may open up ways for in depth study of this topic.